CORRELATION BETWEEN MAGNESIUM AND CALCIUM LEVELS ON HEALTH IN THE ELDERLY WITH DEGENERATIVE TYPE 2 DIABETES MELLITUS - Wijayanti, Christina Destri Wiwis; Ayu, Diva Sukma; Mariska, Nabila Refi (Ridwan Institute, 2025)
Diabetes Mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels due to decreased insulin secretion from pancreatic beta cells or insulin resistance. Magnesium and calcium are essential minerals that play crucial roles in various enzymatic activities, significantly influencing important biological functions, particularly in relation to metabolic syndrome. The purpose of the research is to investigate the correlation between magnesium and calcium levels in the serum of elderly individuals with type 2 diabetes mellitus. The study method is descriptive observation with cross-sectional studies. The examination sample used 25 serum samples of people with diabetes with age inclusion criteria over 50 years old without any other degenerative diseases. The analysis of the data from the results of the study was then carried out by the SpSS test of the relationship between magnesium levels and the condition of type 2 DM, especially in the context of aging and its impact on metabolic health. Based on the examination of magnesium levels using the xylidil blue method, 23 patients (92%) showed normal results, while 2 patients (8%) showed numbers above normal on average. There was no significant relationship between blood sugar and magnesium levels, blood sugar with calcium levels, and between magnesium with calcium with a significance of p 0.058, p 0.179, and p 0,114, respectively. The findings of this study could enhance the understanding of the complex interactions between these essential minerals and their potential roles in managing metabolic syndrome, ultimately contributing to better health outcomes for older adults with DM.